Annual report 2021: CGIAR Research Program on Water, Land and Ecosystems - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2022)
2021 was WLE’s final year – the culmination of a decade of science and impact. Throughout the year we saw the real-world difference made by our flagship projects and watched solutions unfold at landscape and basin scales. We also saw our research flow into larger processes in a year of international action that included the UN Food Systems Summit and high-stakes meetings of the UN Conventions on Climate Change and Biological Diversity.